Pengembangan Tes Keterampilan Proses Sains (KPS) pada Materi Asam Basa Kelas XI SMA/MA - Ilmiah, Ide; Anwar, Muhammad; Herawati, Netti (Program Pasca Sarjana UNM, 2020)
This is a research development. The objective of this study is to develop and discover the validity, practicality, and reliability of the science process skills (KPS) test on Acid Base material in class XI SMA/MA. The instrument development process uses the Plomp’s development model which consists of five phases which include: initial investigation, design, realization/construction, test, evaluation and revision, and implementation. The assessment instruments developed consisted of three aspects being assessed, namely cognitive, affective, and psychomotor aspects. The trial was conducted at SMA Negeri 14 Gowa on students of class XI IPA 4. Validity is obtained based on the resulting validation value category of 2.4 < Ktg ≤ 3.2 so that the results of a valid science process skill assessment instrument were obtained. Reliability was calculated using the Kuder Richardson-20 formula (KR-20) and categorized based on established standards was obtained at 75% so that the results of a reliable science process skill assessment instrument were obtained. Practicality was obtained from the analysis of the questionnaire responses of educators who gave very positive responses and based on the category of value generated by ≥ 61% so that the results of a practical science process skill assessment instrument were obtained. Therefore, science process skills assessment instrument developed has fulfilled aspects of validity, reliability, and practicality and can be used to assess students.